AB0422 Mental disorders and stress in sjögren's syndrome patients. (23rd January 2014) - Shelomkova, O.; Veltishchev, D.; Lisitsyna, T.; Vasiliev, V.; Kovalevskaya, O.; Seravina, O.; Krasnov, V.; Nasonov, E.
Abstract : Background: The primary Sjögren's Syndrome (SS) - a chronic, systemic autoimmune disease, characterized by lymphocytic infiltration of endocrine glands, functional impairment of the salivary and lachrymal glands, which has some common pathogenic links with stress-related mental disorders (MD). The physical and mental well being of the patients with primary SS are significantly reduced. The patients with SS have significantly high scoring rates for anxiety, depression, paranoid ideation and somatization compared to the controls. Objectives: To evaluate the occurrence rate/severity of MD and the influence of stress factors in SS patients. Methods: 50 inpatient women (mean age 46±13.2 yrs) suffering SS were enrolled in the study. MD were diagnosed in accordance with ICD-10 criteria. The severity of depression, anxiety, stress and fatigue were measured with MADRS, HAM-A, PSS-10 and FSS. Results: The acute stress factors and reactions were preceded the SS symptoms in most cases (54%). The variants of stress factors revealed: "danger" (40%), "loss" (38%), "frustration" (16%) and "disaster" (6%). In most cases "loss", "frustration", "disaster" were related to acute and "danger" - chronic reactions (p<0, 05). The adverse experience in childhood (parental deprivation mostly) had 32 (64%) of SS patients (recurrent events - 48%). MD had the significant provocative chronic stress factors in 36 (72%) patients. Mean severity level of stress (PSS10) was 16.9±6.04 points. High levels of daily stress had 17 (34%) of patients. MD were diagnosed in 42 (84%) of SS patients: depressive episode (mild/moderate; single/recurrent, 18%); dysthymia (18%); generalized anxiety disorder (14%); adjustment disorders (16%); schizotypal disorder (18%). Mean severity levels of anxiety and depression were 16.5±6.5 and 17.2±7.9 accordingly. Nearly one-third of patients had applied to psychiatrists in the past. Suicide attempts and suicidal thoughts had 6 (10%) and 10 (20%) patients accordingly before and during the disease. Fatiguewasone ofthe most often symptoms of SS revealed in most cases (60%). The severity of fatigue (Me 4.2±1.9 points) had significant correlations with the severity of anxiety and depression (r=0, 4). Conclusions: The study revealed high occurrence rate of MD, provocative stress factors and childhood adverse experience in SS patients. The results support the stress-diathesis model of mental disorders in patients suffering SS. Disclosure of Interest: None Declared